Institutional Quality Matter and Vietnamese Corporate Debt Maturity - Hoang Thuy Bich Tram, Nguyen; Linh, Tran Thi Thuy (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 33 No 5E, 2017)
This article studies whether firm-level and country-level factors affect to the corporation's debt maturity in case of Vietnam or not. The paper adopts the balance panel data of 267 listed companies on two trading board HOSE and HNX in the period from 2008 to 2015, estimated by FEM, REM, 2SLS and GMM method. To intrinsic factors, research results show that financial leverage and default risk control have high positive statistical significance with the debt maturity, but tangible assets are lower than those factors. In addition, growth opportunities and company quality have negative impacts to the debt maturity. To external factors, the results point out that economic growth, stock market development and governmental regulation's efficiency demonstrate the positive relationship to the debt maturity with fairly low correlation levels. In spite of that, inflation rate, financial development, the rule of law, corruption control and the rights of creditor factors have negative correlations to the debt maturity. Keywords Debt maturity, long-term debt ratio, GMM system, firm-level factors, country-level factors References [1] Barclay, M., Smith, C., Jr., “The maturity structure of corporate debt”, Journal of Finance, 50 (1995), 609-631. [2] Kirch, G., Terra, P.R.S., “Determinants of corporate debt maturity in South America: Do institutional quality and financial development matter?”, Journal of Corporate Finance, 18 (2012) 4, 980-993. [3] Cai, K., Fairchild, R., Guney, Y., “Debt maturity structure of Chinese companies”, Pacific Basin Finance Journal, 16 (2008), 268-297. [4] Deesomsak, R., Paudyal, K. & Pescetto, G., “Debt Maturity Structure and the 1997 Asian Financial Crisis”, Journal of Multinational Financial Management ,19(2009) 1, 26-42. [5] Goyal, V.K., Wang, W., “Debt maturity and asymmetric information: Evidence from default risk changes”, Journal of Financial and Quantitative Analysis, 48 (2013), 789-817. [6] Tesfaye T. Lemma, Minga Negash, “Debt Maturity Choice of a Firm: Evidence from African Countries”, Journal of Business and Policy Research, 7 (2012) 2, 60-92 [7] Sérgio Costaa, Luis M. S. Laureanoa, Raul M. S. Laureanoa, “The debt maturity of Portuguese SMEs: The aftermath of the 2008 financial crisis”, Social and Behavioral Sciences, 150 (2014 ), 172-181. [8] Myers, S. C., “The Capital Structure Puzzle”, Journal of Finance, 39 (1984), 575-592. [9] Lucas, D., and R. L. McDonald, R. L., “Equity Issues and Stock Price Dynamics”, Journal of Finance, 45 (1990),1019-1043. [10] Flannery, M. J., “Asymmetric Information and Risky Debt Maturity Choice”, Journal of Finance, 41 (1986), 19-37. [11] Douglas W. Diamond, “Monitoring and Reputation: The Choice between Bank Loans and Directly Placed Debt”, The Journal of Political Economy, 99 (1991) 4, 689-721. [12] Morris, “On corporate debt maturity strategies”, Journal of Finance, 31 (1976) 1, 29-37. [13] Myers, S. C.,“Determinants of Corporate Borrowings”, The Journal of Finance, 5 (1977), 147-175. [14] Amir Barnea, Robert A. Haugen, Lemma W. Senbet, “A rationale for debt maturity structure and call provisions in the agency theoretic framework”, The Journal of Finance, 35 (1980) 5, 1223-1234. [15] Jensen M. and W. Meckling, “Theory of the Firm: Managerial Behavior, Agency Costs, and Capital Structure”, Journal of Financial Economics, 3 (1976), 305-360. [16] Douglass C. North, “Institutions”, Journal of Economic Perspectives, 5 (1990) 1, 97-112. [17] Meyer, K. E., “Institutions, transaction costs and entry mode choice in Eastern Europe”, Journal of International Business Studies, 32 (2001), 357-67. [18] Barclay, M.J., Marx, L.M., Smith, C.W., “The joint determination of leverage and maturity”, Journal of Corporate Finance, 9 (2003), 149-167. [19] Johnson, S.A., “Debt maturity and the effects of growth opportunities and liquidity risk on leverage”, Review of Financial Studies, 16 (2003), 209-236. [20] Antoniou, A., Guney, Y., Paudyal, K., “The determinants of debt maturity structure: Evidence from France, Germany and the UK”, European Financial Management, 12 (2006) 2, 161-194. [21] Lopez-Gracia, J., Mestre-Barbera, R., “Tax effect on Spanish SME optimum debt maturity structure”, Journal of Business Research, 64 (2011), 649-65. [22] Custódio, C., Ferreira, A., Laureano, L., “Why are US firms using more short-term debt?”, Journal of Financial Economics, 108 (2013) 1, 182-212. [23] El Ghoul, S., Guedhami, O., Pittman, J., Rizeanu, S., “Cross-country evidence on the importance of auditor choice to corporate debt maturity”, Contemporary Accounting Research (2014). [24] Belkhir, M., Ben-Nasr, H., Boubaker, S., “Labor protection and corporate debt maturity: International evidence”, UAE University working paper (2014). [25] Stephan, A., Talavera,O., Tsapin, A., “Corporate debt maturity choice in emerging financial markets”, Quarterly Review of Economics and Finance, 51 (2011), 141-151. [26] Bae, K. H., Goyal, V. K., “Creditor rights, enforcement, and bank loans”, The Journal of Finance, 64 (2009) 2, 823-860. [27] Gonzalez-Mendez, V.M., “Determinants of debt maturity structure across firm size”, Spanish Journal of Finance and Accounting, 17 (2013), 187-209. [28] Mark Hoven Stohs, David C. Mauer, “The Determinants of Corporate Debt Maturity Structure”, Journal of Business, 69 (1996) 3. [29] Scherr, F. C. and Hulburt, H. M., “The Debt Maturity Structure of Small Firms”, Financial Management, 1 (2001), 85-111. [30] Magri, S., “Debt maturity of Italian firms”, Journal of Money, Credit and Banking, 42 2010, 443-463. [31] Oman, C., Köksal, B., “Debt maturity across firm types: Evidence from a major developing economy”, Emerging Markets Review, 30 (2017), 169-199. [32] Awartani, B., Belkhir, M., Boubaker, S., Maghyereh, A., “Corporate debt maturity in the MENA region: Does institutional quality matter?”, International Review of Financial Analysis, 46 (2016), 309-325. [33] Antonios Antoniou, Yilmaz Guney, Krishna Paudyal, The Determinants of Debt Maturity Structure: Evidence from France, Germany and the UK, European Financial Management, 12 (2006) 2, 161-194. [34] Antoniou, A., Guney, Y., Paudyal, K., “The determinants of capital structure: Capital market-oriented versus bank-oriented institutions”, Journal of Financial and Quantitative Analysis, 43 (2008) 1, 59-92. [35] Fan, J. P., Titman, S., Twite, G., “An international comparison of capital structure and debt maturity choices”, Journal of Financial and Quantitative Analysis, 47 (2012) 1, 23. [36] Garcia-Teruel P, Martinez-Solano P., “Short-term debt in Spanish SMEs”, Int Small Bussiness Journal, 25 (2007), 579-602. [37] Giannetti, M., “Do better institutions mitigate agency problems? Evidence from corporate finance choices”, Journal of Financial and Quantitative Analysis, 38 (2003) 1, 185-212. [38] Diamond, W., “Presidential address, committing to commit: Short-term debt when enforcement is costly”, The Journal of Finance, 59 (2004) 4, 1447-1479. [39] Qian, J., Strahan, E., “How laws and institutions shape financial contracts: The case of bank loans”, The Journal of Finance, 62 (2007) 6, 2803-2834. [40] Aris, “Legal systems, capital structure, and debt maturity in developing countries”, Corp. Gov., 24 (2016), 130-144. [41] Cuneyt Orman, Bülent Köksal, “Debt Maturity across Firm Types: Evidence from a Major Developing Economy”, Emerging Markets Review, 30 (2016). [42] Zheng, X., El Ghoul, S., Guedhami, O., Kwok, C., “National culture and corporate debt maturity”, Journal of Banking & Finance, 36 (2012) 2, 468-488. [43] Jun Qian, Philip E. Strahan, “How Laws and Institutions Shape Financial Contracts: The Case of Bank Loans”, The Journal of Finance, 62 (2007) 6, 2803-2834. [44] Vig, V., “Access to collateral and corporate debt structure: Evidence from a natural experiment”, The Journal of Finance, 68 (2013) 3, 881-928. [45] Cho, S., El Ghoul, S., Guedhami, O., Suh, J., “Creditor rights and capital structure: Evidence from international data”, Journal of Corporate Finance, 25 (2014), 40-60. [46] Mark Hoven Stohs, David C Mauer, “The Determinants of Corporate Debt Maturity Structure”, The Journal of Business, 69 (1996) 3, 279-312. [47] Kane, A., A. J. Marcus, R. L. McDonald, “Debt Policy and the Rate of Return Premium to Leverage”, The Journal of Financial and Quantitative Analysis, 20 (1985) 4, 479-499. [48] E. I. Altman, “Corporate financial distress: A complete guide to predicting, avoiding, and dealing with bankruptcy”, New York: John Wiley & Sons, 1983. [49] Mackie-Mason, Jeffrey K., “Do Taxes Affect Corporate Financing Decisions?”, Journal of Finance, 45 (1990) 5, 1471-1493. [50] Djankov, S., C. McLiesh, and A. Shleifer, “Private credit in 129 countries”, Journal of Financial Economics, 84 (2007), 299-329.